TERRITORIAL FEATURES AND THEIR EFFECTIVE USE IN THE CULTIVATION OF VITICULTURE PRODUCTS - Shafkarov, Bakhrom (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores the significance of territorial characteristics and their effective use in the cultivation of viticulture products. Territorial characteristics, including soil composition, climate, topography, biodiversity, and cultural practices, play a crucial role in shaping the quality, flavor profiles, and identity of wines. By understanding and leveraging these characteristics, wine producers can create wines that reflect a sense of place and terroir. The article reviews existing literature on the topic, highlighting the impact of soil composition on grapevine growth and grape quality, the influence of climate on grape ripening and wine characteristics, the role of topography in creating diverse microclimates, the importance of biodiversity in supporting vine health and wine complexity, and the significance of cultural practices in preserving heritage and guiding vineyard management. The effective use of territorial characteristics enables wine producers to differentiate their products, establish a strong sense of provenance, and satisfy the preferences of discerning consumers. The findings emphasize the importance of understanding and harnessing these characteristics to cultivate exceptional viticulture products.